1994
DOI: 10.1139/v94-310
|View full text |Cite
|
Sign up to set email alerts
|

Micellar catalysis in mixed anionic/cationic surfactant systems

Abstract: . Can. J. Chem. 72,2443Chem. 72, (1994.Dye solubility and stopped-flow kinetic studies were conducted in sodium dodecylsulfate/dodecyltrimethylammonium bromide and sodium dodecylsulfate/decyltrimethylammonium bromide micellar solutions with excess anionic surfactant. The enhanced rate in the presence of anionic micelles of the ~i~+~,,,l~~ridine-2-azo-~-dimeth~laniline (PADA) complexation reaction was used as a probe of the mixed micellar situation. PADA solubilities and the kinetic parameters derived through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…4 It has been used as a probe reaction for metal ion reactivities and kinetic studies in micelle solutions. [5][6][7][8][9][10][11][12][13][14][15] It has also been used as a model for metal-ion extraction in surfactant self-assembly systems. [16][17][18] Most complex-formation reactions of divalent first row transition metal ions are too fast to be studied by the stopped-flow method, but Ni 2+ reacts more slowly and can therefore be studied in this way.…”
Section: Introductionmentioning
confidence: 99%
“…4 It has been used as a probe reaction for metal ion reactivities and kinetic studies in micelle solutions. [5][6][7][8][9][10][11][12][13][14][15] It has also been used as a model for metal-ion extraction in surfactant self-assembly systems. [16][17][18] Most complex-formation reactions of divalent first row transition metal ions are too fast to be studied by the stopped-flow method, but Ni 2+ reacts more slowly and can therefore be studied in this way.…”
Section: Introductionmentioning
confidence: 99%
“…The use of micellar systems as reactions media has been broadly studied because of the ability they have to modify the rates and selectivity of reactions and also their ability to solubilize organic substrates . These systems are widely used in emulsion polymerization reactions, as replacement of volatile organic solvents, templates in the synthesis of new materials (specially nanoparticles), and as enzyme models .…”
Section: Introductionmentioning
confidence: 99%
“…The use of micellar systems as reactions media has been broadly studied because of the ability they have to modify the rates and selectivity of reactions and also their ability to solubilize organic substrates. [3][4][5] These systems are widely used in emulsion polymerization reactions, [6] as replacement of volatile organic solvents, templates in the synthesis of new materials (specially nanoparticles), [7,8] and as enzyme models. [9][10][11] In some cases, it has been observed that the use of micellar media results in different products than those obtained in homogeneous media, [12] and there are some reports of enantioselective reactions in the presence of sugar-derived surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…An oppositely charged drugsurfactant pair was selected in order to obtain strong synergistic effects relative to the properties of the individual components in the mixture. 12 Thus, the c.m.c. is generally considerably lower for the oppositely charged mixture than for either the drug or surfactant alone.…”
mentioning
confidence: 95%